K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

22 tháng 8 2017

mọi người giúp mình nha ! 

=3

28 tháng 6 2021

Ta có: x4 + x3 + ax + b = (x2 + x - 2)(x2 + cx + d)

<=> x4 + x3 + ax + b = x4 + cx3 + dx2 + x3 + cx2 + dx - 2x2 - 2cx - 2d

<=> x4 + x3 + ax + b = x4 + (c + 1)x3 + (d + c - 2)x2 + (d - 2c)x - 2d

Đồng nhất hệ số:

 c + 1  = 1

d + c - 2 = 0

d - 2c = a

-2d = b

<=> c = 0

d = 2 + c = 2

a = d - 2c = 2 - 2.0 = 2

b = -2.2 = -4

Vậy a = d = 2; c = 0; b = -4